Gaya Baru Pelayanan Referensi di Perpustakaan - Syarwan Ahmad (Jurnal Adabiya, 2019)
Reference Service is seen as the heart of Libray Service. Reference Service is facilitated by reference librarians, who fulfill the user’s information need. Like other library services, Reference Service has also changed as a consequence of the impact of technology which is evolving in accordance with the changing need of the society. This article aims at discussing some new trends of library reference. This new style of service is broken into four  main areas namely new trends of reference source; new trends of reference interview; collaborative efforts of reference service; library reference service.